Isolation, screening of rhizosphere fungi antagonistic to rice stem rot disease pathogen Sclerotium oryzae catt., - VENKATESWARLU, NAGAM; SIREESHA, ONGOLU; AISHWAYRA, SANI; VIJAYA, TARTTE; SRIRAMULU, ARUGA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The production of antifungal substances by rhizosphere fungi has long been recognized and this knowledge is entering practical life through the use of fungal antagonists to protect crops against their fungal pathogens. Methods: In this study rhizosphere fungi isolation in serial dilution plate technique, and their antimicrobial properties against plant pathogen tested by dual culture, disc diffusion method. Effect of these fungi in seed germination and growth promoting activity was measured in pot culture method. Results and conclusion: Rhizosphere fungi it has become clear that in addition to diffusible substances evidence has accumulated that these bioactive compounds are not only able to promote seed germination and plant growth, but also to strongly inhibit pathogenic fungal growth. As the demand for organic products and the need to render agriculture more sustainable are rising, finding new environmentally friendly crop protection strategies is essential. In this perspective, the newly discovered capacity of fungal bioactive compounds to efficiently repel phytopathogenic fungi in laboratory experiments holds great promise. Keywords: Rhizosphere, Biological control, Sclerotium oryzae, Seed germination.